2018
DOI: 10.1108/ijcst-03-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of laser treatment and industrial washing on denim fabric tension properties

Abstract: Purpose The purpose of this paper is to determine the influence made by complex finishing of denim fabrics, i.e. laser treatment and industrial washing, on the change in tension properties of fabric. Design/methodology/approach Test specimens were treated by a laser JG-10050. Lasers main technological parameters: maximum laser beam power is 65 W, laser types are hermetic and detached CO2, laser tube wavelength is 10.62 µm. The test specimens processed by different laser energy density have been exposed to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Paper, defined traditionally as a thin sheet made from pressed cellulose fibers 3 , is not commonly thought of as a material that shrinks – even though we probably all have some experience with shrinking cotton cloth, another cellulose-based material, when doing laundry 18,19 . However, we have identified two methods for shrinking paper.…”
Section: Introductionmentioning
confidence: 99%
“…Paper, defined traditionally as a thin sheet made from pressed cellulose fibers 3 , is not commonly thought of as a material that shrinks – even though we probably all have some experience with shrinking cotton cloth, another cellulose-based material, when doing laundry 18,19 . However, we have identified two methods for shrinking paper.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature review, in one [15] study related to the influence of denim washing, as industrial properties and washing on fabric properties, the structural features, shrinkage, air permeability, bending rigidity, extensibility, breaking force and elongation, shear rigidity has been determined. Additionally, [16] in other study researchers define mechanical properties of denim garments after enzymatic bio-machine washing processes and it is found that treatment of denim with different enzymes and stones may cause different effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various types of newly introduced denim of exotic designs supplemented with lightness, smoothness and comfortability sensational features have added a new height to the fashion arena [38]. Recently conducted various research works emphasized about the development of various washing treatments for denim processing [39] [40]. So, current research work about the understanding of different washing treatment on various properties like tensile strength, tear strength, dimensional stability to washing, color fastness to washing, color fastness to water, color fastness to perspiration, color fastness to light, color fastness to rubbing, changes in fabric weight for stretch denim fabric will contribute to enrich the scopes of study on denim washing.…”
Section: Introductionmentioning
confidence: 99%